International Comparison of Manifestations and Tendencies of Latent Juvenile Delinquency in Lithuania - Sakalauskas, Gintautas; Kalpokas, Vaidas; Buzaitytė-Kašalynienė, Jolita; Švedaitė-Sakalauskė, Birutė (Socialinė teorija, empirija, politika ir praktika, 2021)
Juvenile delinquency is a universal phenomenon inherent in the process of biological and social maturation characterized by high latency. Although juvenile delinquent behaviour, due to its spontaneity and recklessness, is easily noticeable and not difficult to investigate, it is often not officially recorded because it is primarily addressed through means of informal social control. Various studies show that children from disadvantaged backgrounds are much more likely to fall into a network of formal social control. Thus, the registered juvenile delinquency not only makes up a very small part of the total juvenile delinquency but its structure and socio-demographic indicators of the accused are also distorted by the selectivity and stigmatization of social control. However, when analysing juvenile delinquency in Lithuania, it is still common to present only the number of registered cases, to analyse them, draw certain conclusions based on them alone, and even develop preventative juvenile delinquency programs. This situation is partly due to the Soviet tradition, which still significantly impacts the general approach to criminal behaviour, in which the latency of criminal behaviour was considered not as a natural and inevitable but a negative and to be destroyed phenomenon. On the other hand, there are few studies of latent juvenile delinquency in Lithuania. They are carried out irregularly according to different methodologies and do not always cover the full complexity of juvenile delinquency. In the article manifestations of latent juvenile delinquency, its’ structure and tendencies in Lithuania are analyzed, Lithuanian indicators are also compared with the indicators of other European countries. Despite some differences in the structure of juvenile delinquency between countries, it can be argued that delinquent behavior is common among juveniles living in all countries, and is usually mild and episodic. According to the analyzed indicators, Lithuania stands out with one essential difference – frequent bullying among secondary school students in all age groups.